POST PANDEMIC INVESTMENT FEASIBILITY ANALYSIS WITH FINANCIAL ASPECT OF LUBRICANT MACHINE - Dyah Puspitasari Sunaryo Putri; Rully Nur Dewanti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The increasing demand for medical gloves during covid 19 pandemic has made PT. X decided to make an investment by buying a machine worth a total of 6.7 billion Rupiah for the business of producing lubricant gloves with particles of 100 nanometers in 2020. With the end of the pandemic, the need for lubricants has decreased dramatically in 2022, making PT. X faces a feasibility problem for the investment in the lubricant machine that has been made. This study aims to analyze the feasibility of financial aspects, namely the assessment with the Discounted Payback Period (DPP), Net Present Value (NPV), Benefit Cost Ratio (BCR) and Profitability Index (PI). The analysis was carried out with pessimistic, moderate and optimistic versions of probability. The results of research using the DPP, NPV, BCR, PI methods are not feasible for pessimistic probabilities and are feasible for moderate and optimistic probabilities.